Sports Science and Human Health Different Approaches - Almeida Marinho, Daniel; Neiva, Henrique P.; Johnson, Christopher P.; Mohamudally, Nawaz (IntechOpen, 2020)
In this era of sedentary lifestyles and disruption, sports science can propose solutions to human health matters. There is no doubt about the positive impact of sports on the physical as well as mental health of an individual, by extrapolation to the society at large. But with the advent of the latest technologies in the sports domain, the body of knowledge about sports science and human health is reaching new heights. The "Sports Science and Human Health - Different Approaches" book aims to expose worldwide research and development works in an explicit manner. Readers will appreciate the diversity of the topics, ranging from the use of machine learning in sports science to the psychological impact of sports and sports for peace initiatives. A large section is dedicated to wearable devices like biomechanical devices to gauge motor skills, and other smart devices to assess player performance. Beyond awareness, the multidisciplinary nature of this book is a source of inspiration for the scientific community.